2019
DOI: 10.1096/fj.201800972r
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of placenta‐derived mesenchymal stromal cells: role of exosomes

Abstract: We have established early‐gestation chorionic villus–derived placenta mesenchymal stromal cells (PMSCs) as a potential treatment for spina bifida (SB), a neural tube defect. Our preclinical studies demonstrated that PMSCs have the potential to cure hind limb paralysis in the fetal lamb model of SB via a paracrine mechanism. PMSCs exhibit neuroprotective function by increasing cell number and neurites, as shown by indirect coculture and direct addition of PMSC‐conditioned medium to the staurosporine‐induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 56 publications
3
99
0
Order By: Relevance
“…Additionally, PMSCs secrete high levels of BDNF, HGF and VEGF as measured by ELISA ( Figure 2C). Neuroprotection assays were also performed with PMSCs and it was shown that these cells increase total branching points (fold change 2.01), circulatory length (fold change 1.52) and total segment counts (fold change 1.56) in SH-SY5Y apoptotic cells, which aligns with previous study findings [22]. EVs were then isolated from PMSCs that were shown to have both immunomodulatory and neuroprotective properties.…”
Section: Pmsc and Pmsc-ev Characterizationsupporting
confidence: 85%
See 4 more Smart Citations
“…Additionally, PMSCs secrete high levels of BDNF, HGF and VEGF as measured by ELISA ( Figure 2C). Neuroprotection assays were also performed with PMSCs and it was shown that these cells increase total branching points (fold change 2.01), circulatory length (fold change 1.52) and total segment counts (fold change 1.56) in SH-SY5Y apoptotic cells, which aligns with previous study findings [22]. EVs were then isolated from PMSCs that were shown to have both immunomodulatory and neuroprotective properties.…”
Section: Pmsc and Pmsc-ev Characterizationsupporting
confidence: 85%
“…Neuroprotection assays were performed exactly as previously described [22]. In brief, the SH-SY5Y neuroblastoma cell line was cultured for 24 h. PMSCs were indirectly cultured in hanging well inserts for 24 h. To assess the neuroprotective properties of PMSCs, SH-SY5Y cells were treated with 1 µM staurosporine to induce apoptosis.…”
Section: Neuroprotection Assay By Indirect Coculturementioning
confidence: 99%
See 3 more Smart Citations